Climate information services in the Mekong River Delta, Vietnam: A human-centered design approach. Interview guide for validate phase - Van, Lam Luong; Giraldo, Diana; Giles, James; Muller, Anna; Swaans, Kees; Ramirez Villegas, Julian (2024)
This guideline supports the data collection process for the study "Rice Farmers’ Use of Climate Information in the Mekong River Delta, Vietnam: A Human-Centered Design Approach." It outlines a structured framework for conducting in-depth interviews with individual farmers, emphasising usability testing. The primary objective is to observe how farmers interact with Agro-Climatic Bulletins (ACBs), uncovering challenges and opportunities to improve the product's usability and user experience. The methodology involves farmers reviewing the latest ACB while verbalizing their thought processes, enabling researchers to capture real-time insights into their engagement with the bulletin.